2001
DOI: 10.1046/j.1471-4159.2001.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

The caspase‐derived C‐terminal fragment of βAPP induces caspase‐independent toxicity and triggers selective increase of Aβ42 in mammalian cells

Abstract: During its physiopathological maturation, the b-amyloid precursor protein undergoes several distinct proteolytic events by activities called secretases. In Alzheimer's disease, the main histological hallmark called senile plaque is clearly linked to the overproduction of the amyloid peptides Ab40 and Ab42, two highly aggregable bAPP-derived fragments generated by combined cleavages by b-and g-secretases. Recently, an alternative hydrolytic pathway was described, involving another category of proteolytic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…We previously suggested that a component of Aβ toxicity is APP dependent, and this requires an intact caspase cleavage site in the cytoplasmic domain at position 664 of APP (12,20,38). Further, we showed that forced dimerization of APP led to increased susceptibility to cell death (27).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We previously suggested that a component of Aβ toxicity is APP dependent, and this requires an intact caspase cleavage site in the cytoplasmic domain at position 664 of APP (12,20,38). Further, we showed that forced dimerization of APP led to increased susceptibility to cell death (27).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, this finding would not explain why C99, which does not contain the E2 region, also forms complexes. It is possible that the transmembrane sequence or cytosolic adaptor molecules are able to facilitate APP complex formations as well.We previously suggested that a component of Aβ toxicity is APP dependent, and this requires an intact caspase cleavage site in the cytoplasmic domain at position 664 of APP (12,20,38). Further, we showed that forced dimerization of APP led to increased susceptibility to cell death (27).…”
mentioning
confidence: 96%
“…Both the 3 kDa C31 peptide and the Nterminus APP∆C31 generated by caspase cleavage are toxic. The C31 peptide renders N2a and HEK293T cells more susceptible to apoptotic insult staurosporine and is toxic to primary cultures of neurons or glia and neuronal cell line, TSM1 [43,71,72]. Similarly, APP∆C31 can induce cell death in a number of neuronal and non-neuronal cell lines [73].…”
Section: Caspase-cleaved App Products Are Toxicmentioning
confidence: 99%
“…Furthermore, caspase-independent forms of PCD have been observed in neurodegenerative and lymphatic diseases. Thus, the caspase-derived C-terminal fragment of beta-amyloid precursor (betaAPP) induces caspase-independent toxicity in TSM1 neurons and potentiates the pathogenic betaAPP maturation pathway by increasing selectively a beta42 species in wild-type betaAPP-expressing human cells (Dumanchin-Njock et al, 2001). Complement-mediated cell death induced by rituximab in B-cell lymphoproliferative disorders is mediated in vitro by a caspase-independent mechanism involving the generation of reactive oxygen species (Bellosillo et al, 2001).…”
Section: Rasmentioning
confidence: 99%